Silver-nickel-copper ternary composite electrode of back contact photovoltaic cell and preparation method thereof

CN122995334APending Publication Date: 2026-10-27DAS SOLAR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611090009.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,上述专利中,铝粉/镍粉的用量较少而银粉用量较高,成本仍较高,且铝/镍相对于银,存在电阻相对较高,高温过程中易氧化而导致电阻进一步增加的问题

Benefits of technology

[0066]本发明依托银、镍、铜三种金属材料的差异化性能与协同互补优势,实现了背接触电池电极结构与导电机制的重构,构建出依次层叠的银基欧姆接触层、镍基扩散阻挡层和铜基导电层,从而精准发挥银的优异欧姆接触性能、镍的铜离子扩散阻隔性能和铜的超高导电低成本优势,在完全满足背接触光伏电池电极低接触电阻和高导电稳定性等性能指标的同时,大幅削减了贵金属银的用量,实现了电极极致降本,完美平衡电池光电转换性能、电极长期可靠性与量产经济性,为高效背接触光伏电池的规模化低成本产业化应用提供了全新技术路径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995334A_ABST
    Figure CN122995334A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of silver nickel copper ternary composite electrode of back contact photovoltaic cell and its preparation method, comprising the following steps: silver nickel composite electrode paste is printed on the grid line pattern of back contact photovoltaic cell matrix, after drying, copper electrode paste is overprinted on the grid line pattern of back contact photovoltaic cell matrix, sintering is carried out, and the silver nickel copper ternary composite electrode of back contact photovoltaic cell is obtained;The mass ratio of silver powder, nickel powder in silver nickel composite electrode paste and copper powder in copper electrode paste is 1:(2-4):(8-10).The present application relies on the differential performance and synergistic complementary advantage of silver, nickel and copper, constructs silver-based ohmic contact layer, nickel-based diffusion barrier layer and copper-based conductive layer which are stacked in turn, accurately plays the excellent ohmic contact performance of silver, the copper ion diffusion barrier performance of nickel and the ultra-high conductivity and low cost advantage of copper, meets the low contact resistance and high conductive stability of back contact photovoltaic cell electrode, and greatly reduces the silver consumption, realizes electrode extreme cost reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, and relates to a back-contact photovoltaic cell, and more particularly to a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell and its preparation method. Background Technology

[0002] With the continuous advancement of grid parity and large-scale mass production in the photovoltaic industry, back-contact crystalline silicon cells, with their core advantages of low shading rate and high photoelectric conversion efficiency, are gradually becoming the mainstream development direction of high-efficiency photovoltaic cells. However, the back-contact cell electrodes in the industry still generally adopt pure silver paste or high silver ratio paste preparation processes, which have the core pain points of large consumption of precious metal silver and high raw material costs. This seriously restricts the large-scale popularization of back-contact cells and the process of cost reduction and efficiency improvement. The industry's demand for new electrode preparation technologies with low cost, high performance and high reliability is becoming increasingly urgent.

[0003] CN121908688A discloses a back-contact solar cell, its preparation method, and a photovoltaic module. By increasing the proportion of aluminum powder in the paste, it reduces reliance on expensive silver, thereby reducing manufacturing costs while maintaining cell performance. CN120164656A discloses a silver-nickel conductive paste for BC batteries and its preparation method. This paste uses nickel powder to replace some of the silver powder, significantly reducing costs, increasing reliability, and achieving conversion efficiency superior to or comparable to traditional all-silver electrode pastes. However, in the above patents, the amount of aluminum / nickel powder used is relatively small while the amount of silver powder is relatively high, resulting in still high costs. Furthermore, aluminum / nickel has relatively high resistance compared to silver, and is prone to oxidation at high temperatures, leading to further increases in resistance.

[0004] Therefore, how to develop a new electrode system that can meet the performance indicators of low contact resistance and high conductivity stability of back contact battery electrodes, while also significantly reducing the amount of precious metal silver used, thereby achieving extreme cost reduction of the electrode and balancing the photoelectric conversion performance of the battery, the long-term reliability of the electrode and the economics of mass production, is an urgent problem to be solved in this field. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a silver-nickel-copper ternary composite electrode for back-contact photovoltaic cells and its preparation method. This invention leverages the differentiated properties and synergistic advantages of silver, nickel, and copper to reconstruct the electrode structure and conductivity mechanism of the back-contact cell. It constructs a sequentially stacked silver-based ohmic contact layer, a nickel-based diffusion barrier layer, and a copper-based conductive layer. This precisely utilizes the excellent ohmic contact performance of silver, the copper ion diffusion barrier performance of nickel, and the ultra-high conductivity and low cost advantages of copper. While fully meeting the performance indicators of low contact resistance and high conductivity stability of back-contact photovoltaic cell electrodes, it significantly reduces the amount of precious metal silver used, achieving extreme cost reduction for the electrode. It perfectly balances the photoelectric conversion performance of the cell, the long-term reliability of the electrode, and the economics of mass production, providing a new technical path for the large-scale, low-cost industrial application of high-efficiency back-contact photovoltaic cells.

[0006] To achieve this objective, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell, comprising the following steps:

[0008] Silver-nickel composite electrode paste is printed on the grid line pattern of the back contact photovoltaic cell substrate. After drying, copper electrode paste is overprinted on the grid line pattern of the back contact photovoltaic cell substrate and sintered to obtain the silver-nickel-copper ternary composite electrode of the back contact photovoltaic cell. The mass ratio of silver powder and nickel powder in the silver-nickel composite electrode paste to copper powder in the copper electrode paste is 1:(2~4):(8~10).

[0009] For example, the mass ratio of silver powder and nickel powder in the silver-nickel composite electrode paste to copper powder in the copper electrode paste can be 1:2:8, 1:2:9, 1:2:10, 1:3:8, 1:3:9, 1:3:10, 1:4:8, 1:4:9, or 1:4:10, etc.

[0010] This invention leverages the differentiated properties and synergistic advantages of silver, nickel, and copper to reconstruct the electrode structure and conductivity mechanism of back-contact photovoltaic cells. It constructs a sequentially stacked silver-based ohmic contact layer, a nickel-based diffusion barrier layer, and a copper-based conductive layer. This precisely utilizes the excellent ohmic contact performance of silver, the copper ion diffusion barrier performance of nickel, and the ultra-high conductivity and low cost advantages of copper. While fully meeting the performance indicators of low contact resistance and high conductivity stability of back-contact photovoltaic cell electrodes, it significantly reduces the amount of precious metal silver used, achieving extreme cost reduction for the electrodes. It perfectly balances the photoelectric conversion performance of the battery, the long-term reliability of the electrodes, and the economics of mass production, providing a new technical path for the large-scale, low-cost industrial application of high-efficiency back-contact photovoltaic cells.

[0011] Among them, silver's excellent wettability and electrical properties enable it to form a continuous, dense, and low-resistance ohmic contact interface on the grid pattern of the back contact photovoltaic cell substrate, effectively reducing interface recombination losses and ensuring that the back contact cell has excellent photoelectric conversion performance. Nickel's stable metal lattice structure and extremely low ion migration characteristics enable it to construct a dense copper ion diffusion barrier between the back contact photovoltaic cell substrate and the copper-based conductive layer, effectively inhibiting the migration and penetration of copper elements in the copper-based conductive layer, completely avoiding the risk of cell failure caused by copper diffusion, and significantly improving the long-term service stability and service life of the back contact photovoltaic cell. Copper's intrinsic conductivity is better than that of silver, and the copper-based conductive layer can construct a low-loss current-carrying channel, effectively reducing electrode body resistance and improving the high-current output capability of the back contact photovoltaic cell. Moreover, copper material can replace most of the precious metal silver, which can significantly reduce the amount of precious metal used in the electrode paste and significantly reduce the manufacturing cost.

[0012] Furthermore, by adjusting the mass ratio of silver, nickel, and copper to 1:(2~4):(8~10), a stable and continuous silver-nickel-copper conductive pathway can be constructed, balancing electrode conductivity, oxidation resistance, and material cost. If the nickel content is too low, copper oxidation cannot be effectively blocked, and the interfacial contact resistance will increase significantly; if the nickel content is too high, the overall resistivity of the electrode will increase, reducing conductivity. If the copper content is too low, the cost reduction effect is insufficient, and the continuity of the conductive network is poor; if the copper content is too high, the system's oxidation resistance is insufficient, and the electrical stability and reliability of the electrode will decrease under long-term service.

[0013] It is worth noting that the preparation method provided by the present invention can be adapted to the existing photovoltaic screen printing mass production process without major modifications to the production line, and can effectively control the preparation cost.

[0014] Preferably, the silver-nickel composite electrode paste includes silver powder, nickel powder, first glass powder, first organic carrier, first thixotropic agent, and first dispersant.

[0015] Preferably, in the silver-nickel composite electrode slurry, the mass ratio of silver powder, nickel powder, first glass powder, first organic carrier, first thixotropic agent and first dispersant is 20:(40~80):(1~5):(10~15):(1~3):(1~3).

[0016] For example, the mass ratio of silver powder, nickel powder, first glass powder, first organic carrier, first thixotropic agent and first dispersant can be 20:40:5:15:3:3, 20:61:3:12:2:2, 20:80:1:10:1:1 or 20:60:1:15:2:2, etc.

[0017] Preferably, the copper electrode slurry comprises copper powder, a second glass powder, a second organic carrier, a second thixotropic agent, and a second dispersant.

[0018] Preferably, in the copper electrode slurry, the mass ratio of the copper powder, the second glass powder, the second organic carrier, the second thixotropic agent, and the second dispersant is (60~100):(1~5):(10~15):(1~3):(1~3).

[0019] For example, the mass ratio of copper powder, second glass powder, second organic carrier, second thixotropic agent and second dispersant can be 100:5:15:3:3, 81:3:12:2:2, 60:1:10:1:1 or 80:1:15:2:2, etc.

[0020] Preferably, the first glass powder includes B2O3, SiO2, Bi2O3 and PbO.

[0021] Preferably, in the first glass powder, the mass ratio of B2O3, SiO2, Bi2O3 and PbO is (10~30):(10~30):(5~15):(30~70).

[0022] For example, the mass ratio of B2O3, SiO2, Bi2O3 and PbO can be 10:30:5:70, 30:10:15:30, 20:20:10:50 or 15:25:12:55, etc.

[0023] The first glass powder provided by this invention has a low melting point (≤350℃). By adding the first glass powder to the silver-nickel composite electrode paste, the low-melting-point glass phase has extremely strong surface wetting and spreading ability, and can spontaneously spread on the uneven silicon-based substrate surface, effectively filling the micro-pores, grooves and micron-level gaps between the paste and the substrate on the silicon-based surface, eliminating interfacial pores and contact blind areas, greatly improving the physical adhesion of the paste to the silicon-based surface, and achieving a tightly bonded interface structure.

[0024] Preferably, the second glass powder comprises CuO, SiO2, Mn2O3 and ZnO.

[0025] Preferably, in the second glass powder, the mass ratio of CuO, SiO2, Mn2O3 and ZnO is (10~30):(10~30):(5~15):(30~70).

[0026] For example, the mass ratio of CuO, SiO2, Mn2O3 and ZnO can be 10:30:5:70, 30:10:15:30, 20:20:10:50 or 15:25:12:55, etc.

[0027] The second glass powder provided by this invention has a high melting point (≥500℃) and a high softening viscosity (≥180Pa·s). By adding the second glass powder to the copper electrode slurry, it can be uniformly coated on the surface of the copper powder, thus preventing the copper from being exposed to the air components and effectively preventing the copper from being oxidized and degraded.

[0028] Preferably, the first organic carrier and the second organic carrier each independently comprise a resin and an organic solvent.

[0029] Preferably, in the first organic carrier and the second organic carrier, the mass ratio of the resin to the organic solvent is (1~2):(8~9).

[0030] For example, the mass ratio of resin to organic solvent is 1:9, 2:8, 1.5:8.5, 1:8, or 2:9, etc.

[0031] Preferably, the resin comprises any one or a combination of at least two of ethyl cellulose, cellulose acetate butyrate, or acrylic resin. Typical but non-limiting combinations include combinations of ethyl cellulose and cellulose acetate butyrate, combinations of cellulose acetate butyrate and acrylic resin, combinations of ethyl cellulose and acrylic resin, combinations of ethyl cellulose, cellulose acetate butyrate, and acrylic resin, etc.

[0032] Preferably, the organic solvent includes any one or a combination of at least two of butyl carbitol, butyl carbitol acetate, or hexadecyl alcohol ester. Typical but non-limiting combinations include combinations of butyl carbitol and butyl carbitol acetate, combinations of butyl carbitol acetate and hexadecyl alcohol ester, combinations of butyl carbitol and hexadecyl alcohol ester, combinations of butyl carbitol, butyl carbitol acetate, and hexadecyl alcohol ester, etc.

[0033] Preferably, the first thixotropic agent and the second thixotropic agent each independently comprise fumed silica.

[0034] Preferably, the first dispersant and the second dispersant each independently comprise tallow diamine dioleate (TDO).

[0035] Preferably, the preparation method of the silver-nickel composite electrode paste includes the following steps:

[0036] Silver powder, nickel powder, and a first glass powder are subjected to a first stirring and dispersion treatment to obtain a first mixed powder; a first organic carrier, a first thixotropic agent, a first dispersant, and the first mixed powder are subjected to a first centrifugal dispersion treatment to obtain a first solid-liquid mixed phase; the first solid-liquid mixed phase is subjected to a first grinding and a second centrifugal dispersion treatment to obtain the silver-nickel composite electrode slurry.

[0037] Preferably, the method for preparing the copper electrode paste includes the following steps:

[0038] The copper powder and the second glass powder are subjected to a second stirring and dispersion treatment to obtain a second mixed powder; the second organic carrier, the second thixotropic agent, the second dispersant and the second mixed powder are subjected to a third centrifugal dispersion treatment to obtain a second solid-liquid mixed phase; the second solid-liquid mixed phase is subjected to a second grinding and a fourth centrifugal dispersion treatment to obtain the copper electrode slurry.

[0039] Preferably, the stirring speeds of the first stirring and dispersion treatment and the second stirring and dispersion treatment are independently 50 rpm to 150 rpm, for example, 50 rpm, 80 rpm, 100 rpm, 120 rpm or 150 rpm.

[0040] Preferably, the dispersion speeds of the first stirring and dispersion treatment and the second stirring and dispersion treatment are independently 500 rpm to 1500 rpm, for example, 500 rpm, 800 rpm, 1000 rpm, 1200 rpm or 1500 rpm.

[0041] Preferably, the rotation speeds of the first centrifugal dispersion treatment and the third centrifugal dispersion treatment are independently 3000 rpm to 5000 rpm, for example, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm or 5000 rpm.

[0042] Preferably, the number of times the first centrifugal dispersion treatment and the third centrifugal dispersion treatment are performed independently is 3 to 5 times, for example, 3 times, 4 times or 5 times.

[0043] Preferably, the first grinding and the second grinding are performed independently in a three-roll mill, wherein the speed ratio of the front roller, middle roller and rear roller of the three-roll mill is 5:8:9, and the speed of the middle roller is 400rpm~600rpm, for example, 400rpm, 450rpm, 500rpm, 550rpm or 600rpm.

[0044] Preferably, the rotation speeds of the second centrifugal dispersion treatment and the fourth centrifugal dispersion treatment are independently 4000 rpm to 6000 rpm, for example, 4000 rpm, 4500 rpm, 5000 rpm, 5500 rpm or 6000 rpm.

[0045] Preferably, the second centrifugal dispersion treatment and the fourth centrifugal dispersion treatment are performed independently 2 to 4 times, for example, 2 times, 3 times or 4 times.

[0046] Preferably, the preparation method of the first glass powder includes: first mixing the B2O3, SiO2, Bi2O3 and PbO, and performing a first calcination treatment to obtain a molten glass liquid; placing the molten glass liquid in water for a first water quenching treatment to obtain glass slag; and performing a first ball milling treatment on the glass slag to obtain the first glass powder.

[0047] Preferably, the temperature of the first calcination treatment is 1000℃~1100℃, for example, it can be 1000℃, 1020℃, 1050℃, 1080℃ or 1100℃.

[0048] Preferably, the heating rate of the first calcination treatment is 20℃ / min to 30℃ / min, for example, it can be 20℃ / min, 22℃ / min, 25℃ / min, 28℃ / min or 30℃ / min.

[0049] Preferably, the first calcination treatment time is 30 min to 90 min, for example, it can be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min.

[0050] Preferably, the preparation method of the second glass powder includes: mixing CuO, SiO2, Mn2O3 and ZnO in a second calcination process to obtain a molten glass liquid; placing the molten glass liquid in water for a second water quenching process to obtain glass slag; and subjecting the glass slag to a second ball milling process to obtain the second glass powder.

[0051] Preferably, the temperature of the second calcination treatment is 1200℃~1400℃, for example, it can be 1200℃, 1250℃, 1300℃, 1350℃ or 1400℃.

[0052] Preferably, the heating rate of the second calcination treatment is 10℃ / min to 30℃ / min, for example, it can be 10℃ / min, 15℃ / min, 20℃ / min, 25℃ / min or 30℃ / min.

[0053] Preferably, the second calcination treatment time is 60 min to 120 min, for example, it can be 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min.

[0054] Preferably, the preparation method of the first organic carrier and the second organic carrier includes: stirring and mixing the resin and the organic solvent to obtain the first organic carrier and the second organic carrier.

[0055] Preferably, the stirring speed is 300 r / min to 800 r / min, for example, it can be 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min or 800 r / min.

[0056] Preferably, the mixing temperature is 60℃~90℃, for example, it can be 60℃, 65℃, 70℃, 75℃, 80℃, 85℃ or 90℃.

[0057] Preferably, the mixing time is 8h to 12h, for example, it can be 8h, 9h, 10h, 11h or 12h.

[0058] Preferably, the sintering temperature is 720℃~780℃, for example, it can be 720℃, 730℃, 740℃, 750℃, 760℃, 770℃ or 780℃, etc.

[0059] In this invention, by controlling the sintering temperature to 720℃~780℃, the glass phase can be fully melted, promoting the sintering and interconnection of silver-nickel-copper particles, and achieving good ohmic contact between the electrode and the silicon substrate. If the sintering temperature is too low, the glass melting degree is insufficient, the metal particles are not sufficiently interconnected, the continuity of the conductive path is poor, and the electrode contact resistance increases significantly. If the sintering temperature is too high, copper and nickel are easily oxidized to form high-resistance oxides, excessive flow of molten glass can easily cause gate line deformation, over-etching of edges, and excessive diffusion of metal atoms into the silicon substrate, increasing current recombination losses and reducing the long-term reliability of the device.

[0060] Preferably, the heating rate of the sintering is 3℃ / min to 10℃ / min, for example, it can be 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min or 10℃ / min, etc.

[0061] Preferably, the sintering time is 6h to 12h, for example, it can be 6h, 7h, 8h, 9h, 10h, 11h or 12h.

[0062] In a second aspect, the present invention provides a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell, wherein the silver-nickel-copper ternary composite electrode for the back-contact photovoltaic cell is prepared by the preparation method described in the first aspect.

[0063] The silver-nickel-copper ternary composite electrode comprises a silver-based ohmic contact layer, a nickel-based diffusion barrier layer, and a copper-based conductive layer stacked sequentially.

[0064] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] This invention leverages the differentiated properties and synergistic advantages of silver, nickel, and copper to reconstruct the electrode structure and conductivity mechanism of back-contact photovoltaic cells. It constructs a sequentially stacked silver-based ohmic contact layer, a nickel-based diffusion barrier layer, and a copper-based conductive layer. This precisely utilizes the excellent ohmic contact performance of silver, the copper ion diffusion barrier performance of nickel, and the ultra-high conductivity and low cost advantages of copper. While fully meeting the performance indicators of low contact resistance and high conductivity stability of back-contact photovoltaic cell electrodes, it significantly reduces the amount of precious metal silver used, achieving extreme cost reduction for the electrodes. It perfectly balances the photoelectric conversion performance of the battery, the long-term reliability of the electrodes, and the economics of mass production, providing a new technical path for the large-scale, low-cost industrial application of high-efficiency back-contact photovoltaic cells.

[0067] Among them, silver's excellent wettability and electrical properties enable it to form a continuous, dense, and low-resistance ohmic contact interface on the grid pattern of the back contact photovoltaic cell substrate, effectively reducing interface recombination losses and ensuring that the back contact cell has excellent photoelectric conversion performance. Nickel's stable metal lattice structure and extremely low ion migration characteristics enable it to construct a dense copper ion diffusion barrier between the back contact photovoltaic cell substrate and the copper-based conductive layer, effectively inhibiting the migration and penetration of copper elements in the copper-based conductive layer, completely avoiding the risk of cell failure caused by copper diffusion, and significantly improving the long-term service stability and service life of the back contact photovoltaic cell. Copper's intrinsic conductivity is better than that of silver, and the copper-based conductive layer can construct a low-loss current-carrying channel, effectively reducing electrode body resistance and improving the high-current output capability of the back contact photovoltaic cell. Moreover, copper material can replace most of the precious metal silver, which can significantly reduce the amount of precious metal used in the electrode paste and significantly reduce the manufacturing cost.

[0068] Furthermore, by adjusting the mass ratio of silver, nickel, and copper to 1:(2~4):(8~10), a stable and continuous silver-nickel-copper conductive pathway can be constructed, balancing electrode conductivity, oxidation resistance, and material cost. If the nickel content is too low, copper oxidation cannot be effectively blocked, and the interfacial contact resistance will increase significantly; if the nickel content is too high, the overall resistivity of the electrode will increase, reducing conductivity. If the copper content is too low, the cost reduction effect is insufficient, and the continuity of the conductive network is poor; if the copper content is too high, the system's oxidation resistance is insufficient, and the electrical stability and reliability of the electrode will decrease under long-term service. Attached Figure Description

[0069] Figure 1This is a cross-sectional schematic diagram of the silver-nickel-copper ternary composite electrode and its electron transport according to the present invention. Detailed Implementation

[0070] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0071] The scope of this invention can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form an effective range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this invention. In addition, if the minimum range values ​​1 and 2 are listed, and the maximum range values ​​3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this invention. In this invention, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.

[0072] Unless otherwise specified, the term "at least two combinations" in this invention refers to a quantity greater than or equal to 2. For example, "any one or at least two combinations" means that any one of the listed items can be selected, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this invention.

[0073] In this invention, unless otherwise specified, the feature or solution corresponding to "and / or" covers any one of two or more related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a set consisting of A, B, and combinations of A and B. "Including A and / or B" can be understood, depending on the context of the statement, as including A, including B, or simultaneously including both A and B. In this invention, "optional" means that the corresponding feature, component, step, or solution is not essential, i.e., selected from either "present" or "absent" parallel solutions. If multiple "optional" limitations appear in a technical solution, unless otherwise specified and without technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.

[0074] In this invention, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond the listed elements unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A may consist only of a1, a2, and a3, or it may include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements."

[0075] All embodiments and optional embodiments of the present invention, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of the present invention. The term "embodiment" as used in this invention means that a specific feature, structure, or characteristic described in connection with an embodiment can be included in at least one embodiment or implementation of the present invention. The appearance of this phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art can explicitly and implicitly understand that the embodiments described in this invention can be combined with other embodiments without technical conflict.

[0076] In this invention, the ordinal numbers “first,” “second,” “third,” and “fourth” used in expressions such as “first aspect,” “second aspect,” “third aspect,” and “fourth aspect” are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.

[0077] In this invention, the order in which the steps are written in the methods described in each embodiment does not imply a strict execution order. The actual execution order of each step should be determined based on its function and possible internal logic. Unless otherwise specified, all steps of this invention can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.

[0078] Figure 1 This is a cross-sectional schematic diagram of the silver-nickel-copper ternary composite electrode of the present invention and its electron transport. It can be seen that the silver-nickel-copper ternary composite electrode includes a silver-based ohmic contact layer, a nickel-based diffusion barrier layer and a copper-based conductive layer stacked sequentially. The electron transport path is from the substrate to the silver-based ohmic contact layer, the nickel-based diffusion barrier layer and the copper-based conductive layer in sequence.

[0079] Example 1

[0080] This embodiment provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell, including the following steps:

[0081] (1) According to the mass fractions, 20 parts B2O3, 20 parts SiO2, 10 parts Bi2O3 and 50 parts PbO are mixed evenly and placed into a ceramic crucible and transferred together to a muffle furnace. The temperature is raised to 1050℃ at a heating rate of 25℃ / min and calcined for 60min to obtain molten glass. The molten glass is placed in a steel tank filled with water for water quenching to obtain glass slag. The glass slag is ball-milled and then classified by particle size to obtain the first glass powder.

[0082] (2) According to the mass fractions, 20 parts CuO, 20 parts SiO2, 10 parts Mn2O3 and 50 parts ZnO are mixed evenly and placed into a ceramic crucible and transferred together to a muffle furnace. The temperature is raised to 1300℃ at a heating rate of 20℃ / min and calcined for 90min to obtain molten glass. The molten glass is placed in a steel tank filled with water for water quenching to obtain glass slag. The glass slag is ball-milled and then classified by particle size to obtain second glass powder.

[0083] (3) According to the mass fractions, 8 parts of ethyl cellulose, 4 parts of cellulose acetate butyrate, 2 parts of acrylic resin, 20 parts of butyl carbitol, 20 parts of alcohol ester hexadecyl and 50 parts of butyl carbitol acetate are mixed evenly and placed into a high-speed mixer. The mixture is stirred for 10 hours at a temperature of 75°C and a speed of 500 r / min to obtain the first organic carrier and the second organic carrier.

[0084] (4) According to the mass fraction, 20 parts of silver powder, 61 parts of nickel powder and 3 parts of first glass powder are put into a stirrer and stirred and dispersed at a stirring speed of 100 rpm and a dispersion speed of 1000 rpm to obtain the first mixed powder; 12 parts of the first organic carrier, 2 parts of the first thixotropic agent (fumed silica), 2 parts of the first dispersant (TDO) and the first mixed powder are put into a centrifugal disperser and centrifuged and dispersed 5 times at a speed of 4000 rpm to obtain the first solid-liquid mixed phase; the first solid-liquid mixed phase is put into a three-roll mill for grinding (the speed ratio of the front roller, middle roller and rear roller of the three-roll mill is 5:8:9, and the speed of the middle roller is 500 rpm), and after grinding, it is put into a centrifugal disperser again and centrifuged and dispersed 3 times at a speed of 5000 rpm to obtain silver-nickel composite electrode slurry.

[0085] (5) According to the mass fraction, 81 parts of copper powder and 3 parts of second glass powder are put into a stirrer and stirred and dispersed at a stirring speed of 100 rpm and a dispersion speed of 1000 rpm to obtain a second mixed powder; 12 parts of second organic carrier, 2 parts of second thixotropic agent (fumed silica), 2 parts of second dispersant (TDO) and the second mixed powder are put into a centrifugal disperser and centrifuged and dispersed 5 times at a speed of 4000 rpm to obtain a second solid-liquid mixed phase; the second solid-liquid mixed phase is put into a three-roll mill for grinding (the speed ratio of the front roller, middle roller and rear roller of the three-roll mill is 5:8:9, and the speed of the middle roller is 500 rpm), and after grinding, it is put into a centrifugal disperser again and centrifuged and dispersed 3 times at a speed of 5000 rpm to obtain copper electrode slurry.

[0086] (6) Using screen printing technology, 50 mg of silver-nickel composite electrode paste is printed on the grid line pattern of the back contact photovoltaic cell substrate. After drying, 120 mg of copper electrode paste is overprinted on the grid line pattern of the back contact photovoltaic cell substrate. Then, it is transferred to the Despatch sintering furnace, heated to 750°C at a heating rate of 5°C / min and sintered for 9 hours to obtain the silver-nickel-copper ternary composite electrode of the back contact photovoltaic cell.

[0087] Example 2

[0088] This embodiment provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell, including the following steps:

[0089] (1) According to the mass fractions, 10 parts B2O3, 30 parts SiO2, 5 parts Bi2O3 and 55 parts PbO are mixed evenly and placed into a ceramic crucible and transferred together to a muffle furnace. The temperature is raised to 1100℃ at a heating rate of 30℃ / min and calcined for 30min to obtain molten glass. The molten glass is placed in a steel tank filled with water for water quenching to obtain glass slag. The glass slag is ball-milled and then classified by particle size to obtain the first glass powder.

[0090] (2) According to the mass fractions, 10 parts CuO, 30 parts SiO2, 5 parts Mn2O3 and 55 parts ZnO are mixed evenly and placed into a ceramic crucible and transferred together to a muffle furnace. The temperature is raised to 1400℃ at a heating rate of 30℃ / min and calcined for 60min to obtain molten glass. The molten glass is placed in a steel tank filled with water for water quenching to obtain glass slag. The glass slag is ball-milled and then classified by particle size to obtain second glass powder.

[0091] (3) According to the mass fractions, 6 parts of ethyl cellulose, 2 parts of cellulose acetate butyrate, 2 parts of acrylic resin, 30 parts of butyl carbitol, 30 parts of hexadecyl alcohol ester and 30 parts of butyl carbitol acetate are mixed evenly and placed into a high-speed mixer. The mixture is stirred for 8 hours at a temperature of 90℃ and a speed of 800r / min to obtain the first organic carrier and the second organic carrier.

[0092] (4) According to the mass fraction, 20 parts of silver powder, 40 parts of nickel powder and 1 part of the first glass powder are put into a stirrer and stirred and dispersed at a stirring speed of 50 rpm and a dispersion speed of 500 rpm to obtain the first mixed powder; 10 parts of the first organic carrier, 1 part of the first thixotropic agent (fumed silica), 1 part of the first dispersant (TDO) and the first mixed powder are put into a centrifugal disperser and centrifuged and dispersed 3 times at a speed of 3000 rpm to obtain the first solid-liquid mixed phase; the first solid-liquid mixed phase is put into a three-roll mill for grinding (the speed ratio of the front roller, middle roller and rear roller of the three-roll mill is 5:8:9, and the speed of the middle roller is 400 rpm), and after grinding, it is put into a centrifugal disperser again and centrifuged and dispersed 2 times at a speed of 4000 rpm to obtain silver-nickel composite electrode slurry.

[0093] (5) According to the mass fraction, 60 parts of copper powder and 1 part of second glass powder are put into a stirrer and stirred and dispersed at a stirring speed of 50 rpm and a dispersion speed of 500 rpm to obtain a second mixed powder; 10 parts of second organic carrier, 1 part of second thixotropic agent (fumed silica), 1 part of second dispersant (TDO) and the second mixed powder are put into a centrifugal disperser and centrifuged and dispersed 3 times at a speed of 3000 rpm to obtain a second solid-liquid mixed phase; the second solid-liquid mixed phase is put into a three-roll mill for grinding (the speed ratio of the front roller, middle roller and rear roller of the three-roll mill is 5:8:9, and the speed of the middle roller is 400 rpm), and after grinding, it is put into a centrifugal disperser again and centrifuged and dispersed 2 times at a speed of 4000 rpm to obtain copper electrode slurry.

[0094] (6) Using screen printing technology, 50 mg of silver-nickel composite electrode paste was printed on the grid line pattern of the back contact photovoltaic cell substrate. After drying, 130 mg of copper electrode paste was overprinted on the grid line pattern of the back contact photovoltaic cell substrate. Then, it was transferred to the Despatch sintering furnace, heated to 720°C at a heating rate of 3°C / min, and sintered for 6 hours to obtain the silver-nickel-copper ternary composite electrode of the back contact photovoltaic cell.

[0095] Example 3

[0096] This embodiment provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell, including the following steps:

[0097] (1) According to the mass fractions, 30 parts B2O3, 10 parts SiO2, 15 parts Bi2O3 and 45 parts PbO are mixed evenly and placed into a ceramic crucible and transferred together to a muffle furnace. The temperature is raised to 1000℃ at a heating rate of 20℃ / min and calcined for 90min to obtain molten glass. The molten glass is placed in a steel tank filled with water for water quenching to obtain glass slag. The glass slag is ball-milled and then classified by particle size to obtain the first glass powder.

[0098] (2) According to the mass fractions, 30 parts CuO, 10 parts SiO2, 15 parts Mn2O3 and 45 parts ZnO are mixed evenly and placed into a ceramic crucible and transferred together to a muffle furnace. The temperature is raised to 1200℃ at a heating rate of 10℃ / min and calcined for 120min to obtain molten glass. The molten glass is placed in a steel tank filled with water for water quenching to obtain glass slag. The glass slag is ball-milled and then classified by particle size to obtain second glass powder.

[0099] (3) According to the mass fractions, 10 parts of ethyl cellulose, 6 parts of cellulose acetate butyrate, 4 parts of acrylic resin, 20 parts of butyl carbitol, 30 parts of hexadecyl alcohol ester and 30 parts of butyl carbitol acetate are mixed evenly and placed into a high-speed mixer. The mixture is stirred for 12 hours at a temperature of 60°C and a speed of 300 r / min to obtain the first organic carrier and the second organic carrier.

[0100] (4) According to the mass fraction, 20 parts of silver powder, 80 parts of nickel powder and 5 parts of first glass powder are put into a stirrer and stirred and dispersed at a stirring speed of 150 rpm and a dispersion speed of 1500 rpm to obtain the first mixed powder; 15 parts of the first organic carrier, 3 parts of the first thixotropic agent (fumed silica), 3 parts of the first dispersant (TDO) and the first mixed powder are put into a centrifugal disperser and centrifuged and dispersed 4 times at a speed of 5000 rpm to obtain the first solid-liquid mixed phase; the first solid-liquid mixed phase is put into a three-roll mill for grinding (the speed ratio of the front roller, middle roller and rear roller of the three-roll mill is 5:8:9, and the speed of the middle roller is 600 rpm), and after grinding, it is put into a centrifugal disperser again and centrifuged and dispersed 4 times at a speed of 6000 rpm to obtain silver-nickel composite electrode slurry.

[0101] (5) According to the mass fraction, 100 parts of copper powder and 5 parts of second glass powder are put into a stirrer and stirred and dispersed at a stirring speed of 150 rpm and a dispersion speed of 1500 rpm to obtain a second mixed powder; 15 parts of second organic carrier, 3 parts of second thixotropic agent (fumed silica), 3 parts of second dispersant (TDO) and the second mixed powder are put into a centrifugal disperser and centrifuged and dispersed 4 times at a speed of 5000 rpm to obtain a second solid-liquid mixed phase; the second solid-liquid mixed phase is put into a three-roll mill for grinding (the speed ratio of the front roller, middle roller and rear roller of the three-roll mill is 5:8:9, and the speed of the middle roller is 600 rpm), and after grinding, it is put into a centrifugal disperser again and centrifuged and dispersed 4 times at a speed of 6000 rpm to obtain copper electrode slurry.

[0102] (6) Using screen printing technology, 50 mg of silver-nickel composite electrode paste is printed on the grid line pattern of the back contact photovoltaic cell substrate. After drying, 100 mg of copper electrode paste is overprinted on the grid line pattern of the back contact photovoltaic cell substrate. Then, it is transferred to the Despatch sintering furnace, heated to 780°C at a heating rate of 10°C / min and sintered for 12 h to obtain the silver-nickel-copper ternary composite electrode of the back contact photovoltaic cell.

[0103] Example 4

[0104] This embodiment provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell. Except for step (4), in which the first glass powder is not added, all other steps are the same as in embodiment 1.

[0105] Example 5

[0106] This embodiment provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell. Except for step (5), in which the second glass powder is not added, all other steps are the same as in Example 1.

[0107] Example 6

[0108] This embodiment provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell. Except for adjusting the sintering temperature in step (6) to 700°C, all other steps are the same as in Example 1.

[0109] Example 7

[0110] This embodiment provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell. Except for adjusting the sintering temperature in step (6) to 800°C, all other steps are the same as in Example 1.

[0111] Comparative Example 1

[0112] This comparative example provides a method for preparing a silver electrode for a back-contact photovoltaic cell. Except for steps (2) and (5), step (4) without adding nickel powder and adjusting the mass fraction of silver powder to 81 parts (the total mass fraction of silver powder and nickel powder), and step (6) without overprinting copper electrode paste and adjusting the mass of silver-nickel composite electrode paste to 170 mg (the total mass of silver-nickel composite electrode paste and copper electrode paste), all other steps are the same as in Example 1.

[0113] Comparative Example 2

[0114] This comparative example provides a method for preparing a copper electrode for a back-contact photovoltaic cell. Except for steps (1) and (4), and in step (6) the copper electrode paste is directly printed on the grid pattern of the back-contact photovoltaic cell substrate instead of printing the silver-nickel composite electrode paste, and the mass of the copper electrode paste is adjusted to 170 mg (the total mass of the silver-nickel composite electrode paste and the copper electrode paste), everything else is the same as in Example 1.

[0115] Comparative Example 3

[0116] This comparative example provides a method for preparing a silver-nickel composite electrode for a back-contact photovoltaic cell. Except for not performing steps (2) and (5) and not printing copper electrode paste in step (6), and adjusting the mass of the silver-nickel composite electrode paste to 170 mg (the total mass of the silver-nickel composite electrode paste and the copper electrode paste), everything else is the same as in Example 1.

[0117] Comparative Example 4

[0118] This comparative example provides a method for preparing a silver-copper composite electrode for a back-contact photovoltaic cell. Except for step (4), in which nickel powder is not added and the mass fraction of silver powder is adjusted to 81 parts (the total mass fraction of silver powder and nickel powder), everything else is the same as in Example 1.

[0119] Comparative Example 5

[0120] This comparative example provides a method for preparing a nickel-copper composite electrode for a back-contact photovoltaic cell. Except for step (4), in which silver powder is not added and the mass fraction of nickel powder is adjusted to 81 parts (the total mass fraction of silver powder and nickel powder), everything else is the same as in Example 1.

[0121] Comparative Example 6

[0122] This comparative example provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell. Except for adjusting the mass of the copper electrode slurry in step (6) to 86 mg, all other steps are the same as in Example 1.

[0123] Comparative Example 7

[0124] This comparative example provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell. Except for adjusting the mass of the copper electrode slurry in step (6) to 136 mg, all other steps are the same as in Example 1.

[0125] Comparative Example 8

[0126] This comparative example provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell. Except for adjusting the mass fractions of silver powder and nickel powder in step (4) to 40.5 parts and 40.5 parts respectively, all other steps are the same as in Example 1.

[0127] Comparative Example 9

[0128] This comparative example provides a method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell. Except for adjusting the mass fractions of silver powder and nickel powder in step (4) to 13.5 parts and 67.5 parts respectively, all other steps are the same as in Example 1.

[0129] Cost calculations and cell efficiency tests were performed on the silver-nickel-copper electrodes of the back-contact photovoltaic cells obtained in Examples 1-7 and Comparative Examples 1-9. The results are shown in Table 1.

[0130]

[0131] As can be seen from Table 1, the method for preparing the silver-nickel-copper ternary composite electrode for back-contact photovoltaic cells provided by the present invention can significantly reduce costs without sacrificing cell efficiency.

[0132] Compared with Example 1, the silver-nickel composite electrode slurry in Example 4 does not contain the first glass powder, and the copper electrode slurry in Example 5 does not contain the second glass powder. Not only is the cost not effectively controlled, but also, due to the lack of the wetting and sintering promoting effect of the molten glass phase on the metal particles, the metal powder is difficult to form a dense and continuous conductive network, and the internal contact resistance of the electrode increases significantly. At the same time, it is impossible to complete the controllable etching of the passivation layer on the silicon wafer surface with the help of the glass phase, and it is difficult for the electrode and the silicon substrate to form a stable ohmic contact. The interface contact resistance increases significantly, ultimately leading to a decrease in battery efficiency.

[0133] Compared with Example 1, in Examples 6 and 7, the sintering temperature was adjusted. In Example 6, the sintering temperature was lower than the preferred range, resulting in insufficient melting of the glass powder, making it difficult to effectively wet the silver, nickel, and copper metal particles. The interconnection of the metal particles was insufficient, failing to form a continuous low-resistance conductive path. At the same time, the glass had insufficient etching ability relative to the silicon nitride passivation layer, resulting in poor ohmic contact between the electrode and the silicon substrate. In Example 7, the sintering temperature was higher than the preferred range, making it easy for the copper and nickel components to undergo high-temperature oxidation to generate high-resistance oxides. The excessive fluidity of the molten glass caused excessive erosion, and the excessive diffusion of metal atoms into the silicon substrate exacerbated the current-carrying recombination loss, significantly increasing the series resistance and reducing the battery efficiency.

[0134] Compared with Example 1, Comparative Examples 1 to 9, due to the adjustment of the slurry type or the mass ratio of silver, nickel and copper in the silver-nickel-copper ternary composite electrode, could not give full play to the differentiated properties and synergistic complementary advantages of the three metal materials, resulting in higher costs and lower battery efficiency.

[0135] Using the electrodes of the back-contact photovoltaic cell obtained in Comparative Example 1 as a reference, the open-circuit voltage, short-circuit current, fill factor, and conversion efficiency of the electrodes of the back-contact photovoltaic cells obtained in Examples 1 to 7 and Comparative Examples 2 to 9 were tested. The results are shown in Table 2.

[0136]

[0137] As can be seen from Table 2, the method for preparing the silver-nickel-copper ternary composite electrode for back-contact photovoltaic cells provided by the present invention reduces the cost of a single cell by more than 80%, while the core electrical performance of the cell not only remains unaffected but also shows a slight improvement compared to the pure silver paste benchmark.

[0138] Compared with Example 1, the silver-nickel composite electrode paste in Example 4 does not contain the first glass powder, and the copper electrode paste in Example 5 does not contain the second glass powder. The lack of the wetting and bonding effect of the glass phase on the metal particles and the ability to control the interface makes it difficult for the metal powder to be fully sintered and interconnected to form a continuous conductive network. At the same time, it is impossible to achieve controllable etching of the passivation layer on the silicon wafer surface. It is difficult to build a stable low-resistance ohmic contact between the electrode and the silicon substrate. Furthermore, the copper component lacks the protection of the glass phase during high-temperature sintering and is easily oxidized to form high-resistance oxides. The overall series resistance of the electrode increases significantly, resulting in a decrease in the photoelectric conversion efficiency of the photovoltaic cell.

[0139] Compared with Example 1, in Examples 6 and 7, the sintering temperature was adjusted. In Example 6, the sintering temperature was lower than the preferred range, resulting in insufficient melting of the glass powder, making it difficult to effectively wet the silver, nickel, and copper metal particles. The interconnection of the metal particles was insufficient, failing to form a continuous low-resistance conductive path. At the same time, the glass had insufficient etching ability relative to the silicon nitride passivation layer, resulting in poor ohmic contact between the electrode and the silicon substrate. In Example 7, the sintering temperature was higher than the preferred range, making it easy for the copper and nickel components to undergo high-temperature oxidation to generate high-resistance oxides. The excessive fluidity of the molten glass caused excessive etching, and the excessive diffusion of metal atoms into the silicon substrate exacerbated the current-carrying recombination loss, significantly increasing the series resistance and reducing the photoelectric conversion efficiency of the photovoltaic cell.

[0140] Compared with Example 1, Comparative Examples 1 to 9, due to the adjustment of the slurry type or the mass ratio of silver, nickel and copper in the silver-nickel-copper ternary composite electrode, could not give full play to the differentiated properties and synergistic complementary advantages of the three metal materials, resulting in higher costs and affecting the core electrical performance of the battery.

[0141] The contact resistivity of the electrodes of the back-contact photovoltaic cells obtained in Example 1 and Comparative Example 1 was tested. The results are shown in Table 3.

[0142]

[0143] The contact resistivity test results show that the contact resistivity of the silver-nickel-copper ternary composite electrode obtained in Example 1 is at the same level as that of the silver electrode in Comparative Example 1, and the linear fitting correlation coefficients of the two both reach 0.999. This indicates that the introduction of nickel as a diffusion barrier layer in this invention does not have a negative impact on the Ag-Si ohmic contact interface, and the electrode still maintains excellent low-resistivity contact performance.

[0144] Line resistivity tests were performed on the electrodes of the back-contact photovoltaic cells obtained in Example 1 and Comparative Examples 1 to 3. The results are shown in Table 4.

[0145]

[0146] The results of the linear resistivity test show that the linear resistivity of the silver-nickel-copper ternary composite electrode obtained in Example 1 did not show a significant increase, indicating excellent overprinting stability and no mismatch at the interface between the two types of pastes. The linear resistivity of the copper electrode obtained in Comparative Example 2 did not increase further, indicating that the high-melting-point glass powder improved the oxidation resistance of copper, and no decrease in linear resistivity occurred due to copper oxidation. The linear resistivity of the silver-nickel composite electrode obtained in Comparative Example 3 showed a significant increase, which is due to the inferior conductivity of nickel compared to copper and silver.

[0147] The etching of the silicon substrate was tested on the electrodes of the back-contact photovoltaic cells obtained in Example 1 and Comparative Examples 1 to 3. The results are shown in Table 5.

[0148]

[0149] The etching results of the silicon substrate show that, when silver-nickel composite electrode paste is used as the bottom layer, the glass phase system reacts mildly and controllably with the silicon substrate interface, achieving good ohmic contact without causing etching damage to the silicon wafer. When copper electrode paste is used as the top layer, it does not cause secondary damage to the contact structure of the bottom layer during sintering, demonstrating excellent interface compatibility and reliable interface contact in the composite overlay process. However, when copper electrode paste is used as the bottom layer, copper ions diffuse into the silicon substrate during sintering, damaging the passivation layer on the silicon surface and causing damage to the silicon substrate. This leads to a significant increase in carrier recombination, manifested as localized darkening of the photoluminescence (PL). This is also the reason for the significant decline in the electrical performance of the copper electrode.

[0150] Furthermore, the Cu content on the silicon substrate side of the electrodes of the back-contact photovoltaic cells obtained in Example 1 and Comparative Example 3 was tested. The results are shown in Table 6.

[0151]

[0152] The test results of the Cu content on the silicon substrate side show that the copper content on the silicon substrate side of the electrode of the back contact photovoltaic cell obtained in Example 1 is only 0.01%, while the copper content on the silicon substrate side of the electrode of the back contact photovoltaic cell obtained in Comparative Example 3 reaches 1.58%. The higher the Cu content, the more serious the diffusion of copper ions into the silicon substrate, which further confirms that when the copper electrode paste is used as the bottom layer, copper ions diffuse into the silicon substrate during the sintering process.

[0153] In summary, by leveraging the differentiated properties and synergistic advantages of silver, nickel, and copper, the electrode structure and conductivity mechanism of back-contact photovoltaic cells have been reconstructed. This involves constructing a sequentially stacked silver-based ohmic contact layer, a nickel-based diffusion barrier layer, and a copper-based conductive layer. This precisely utilizes the excellent ohmic contact performance of silver, the copper ion diffusion barrier performance of nickel, and the ultra-high conductivity and low cost advantages of copper. While fully meeting the performance indicators of low contact resistance and high conductivity stability of back-contact photovoltaic cell electrodes, the amount of precious metal silver used has been significantly reduced, achieving extreme cost reduction for the electrodes. This perfectly balances the photoelectric conversion performance of the battery, the long-term reliability of the electrodes, and the economics of mass production, providing a new technical path for the large-scale, low-cost industrial application of high-efficiency back-contact photovoltaic cells.

[0154] Among them, silver's excellent wettability and electrical properties enable it to form a continuous, dense, and low-resistance ohmic contact interface on the grid pattern of the back contact photovoltaic cell substrate, effectively reducing interface recombination losses and ensuring that the back contact cell has excellent photoelectric conversion performance. Nickel's stable metal lattice structure and extremely low ion migration characteristics enable it to construct a dense copper ion diffusion barrier between the back contact photovoltaic cell substrate and the copper-based conductive layer, effectively inhibiting the migration and penetration of copper elements in the copper-based conductive layer, completely avoiding the risk of cell failure caused by copper diffusion, and significantly improving the long-term service stability and service life of the back contact photovoltaic cell. Copper's intrinsic conductivity is better than that of silver, and the copper-based conductive layer can construct a low-loss current-carrying channel, effectively reducing electrode body resistance and improving the high-current output capability of the back contact photovoltaic cell. Moreover, copper material can replace most of the precious metal silver, which can significantly reduce the amount of precious metal used in the electrode paste and significantly reduce the manufacturing cost.

[0155] Furthermore, by adjusting the mass ratio of silver, nickel, and copper to 1:(2~4):(8~10), a stable and continuous silver-nickel-copper conductive pathway can be constructed, balancing electrode conductivity, oxidation resistance, and material cost. If the nickel content is too low, copper oxidation cannot be effectively blocked, and the interfacial contact resistance will increase significantly; if the nickel content is too high, the overall resistivity of the electrode will increase, reducing conductivity. If the copper content is too low, the cost reduction effect is insufficient, and the continuity of the conductive network is poor; if the copper content is too high, the system's oxidation resistance is insufficient, and the electrical stability and reliability of the electrode will decrease under long-term service.

[0156] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell, characterized in that, Includes the following steps: Silver-nickel composite electrode paste is printed on the grid line pattern of the back contact photovoltaic cell substrate. After drying, copper electrode paste is overprinted on the grid line pattern of the back contact photovoltaic cell substrate and sintered to obtain the silver-nickel-copper ternary composite electrode of the back contact photovoltaic cell. The mass ratio of silver powder and nickel powder in the silver-nickel composite electrode paste to copper powder in the copper electrode paste is 1:(2~4):(8~10).

2. The preparation method according to claim 1, characterized in that, The silver-nickel composite electrode paste includes silver powder, nickel powder, first glass powder, first organic carrier, first thixotropic agent, and first dispersant; Preferably, in the silver-nickel composite electrode slurry, the mass ratio of silver powder, nickel powder, first glass powder, first organic carrier, first thixotropic agent and first dispersant is 20:(40~80):(1~5):(10~15):(1~3):(1~3); Preferably, the copper electrode slurry comprises copper powder, a second glass powder, a second organic carrier, a second thixotropic agent, and a second dispersant; Preferably, in the copper electrode slurry, the mass ratio of the copper powder, the second glass powder, the second organic carrier, the second thixotropic agent, and the second dispersant is (60~100):(1~5):(10~15):(1~3):(1~3); Preferably, the first glass powder comprises B2O3, SiO2, Bi2O3, and PbO; Preferably, in the first glass powder, the mass ratio of B2O3, SiO2, Bi2O3 and PbO is (10~30):(10~30):(5~15):(30~70); Preferably, the second glass powder comprises CuO, SiO2, Mn2O3, and ZnO; Preferably, in the second glass powder, the mass ratio of CuO, SiO2, Mn2O3 and ZnO is (10~30):(10~30):(5~15):(30~70); Preferably, the first organic carrier and the second organic carrier each independently comprise a resin and an organic solvent; Preferably, in the first organic carrier and the second organic carrier, the mass ratio of the resin to the organic solvent is (1~2):(8~9); Preferably, the resin comprises any one or a combination of at least two of ethyl cellulose, cellulose acetate butyrate, or acrylic resin; Preferably, the organic solvent includes any one or a combination of at least two of butyl carbitol, butyl carbitol acetate, or hexadecyl alcohol ester; Preferably, the first thixotropic agent and the second thixotropic agent each independently comprise fumed silica; Preferably, the first dispersant and the second dispersant each independently comprise tallow diamine dioleate.

3. The preparation method according to claim 2, characterized in that, The preparation method of the silver-nickel composite electrode paste includes the following steps: Silver powder, nickel powder, and first glass powder are subjected to a first stirring and dispersion treatment to obtain a first mixed powder; The first organic carrier, the first thixotropic agent, the first dispersant and the first mixed powder are subjected to a first centrifugal dispersion treatment to obtain a first solid-liquid mixed phase; The first solid-liquid mixture is subjected to a first grinding and a second centrifugal dispersion treatment to obtain the silver-nickel composite electrode slurry.

4. The preparation method according to claim 2, characterized in that, The preparation method of the copper electrode paste includes the following steps: The copper powder and the second glass powder are subjected to a second stirring and dispersion treatment to obtain a second mixed powder; The second organic carrier, the second thixotropic agent, the second dispersant and the second mixed powder are subjected to a third centrifugal dispersion treatment to obtain a second solid-liquid mixed phase; The second solid-liquid mixture is subjected to a second grinding and a fourth centrifugal dispersion treatment to obtain the copper electrode slurry.

5. The preparation method according to claim 3 or 4, characterized in that, The stirring speeds for the first stirring and dispersion treatment and the second stirring and dispersion treatment are independently 50 rpm to 150 rpm; Preferably, the dispersion speeds of the first stirring and dispersion treatment and the second stirring and dispersion treatment are each independently 500 rpm to 1500 rpm; Preferably, the rotation speeds of the first centrifugal dispersion treatment and the third centrifugal dispersion treatment are each independently 3000 rpm to 5000 rpm; Preferably, the first centrifugal dispersion treatment and the third centrifugal dispersion treatment are performed independently 3 to 5 times each; Preferably, the first grinding and the second grinding are performed independently in a three-roll mill, wherein the speed ratio of the front roller, middle roller and rear roller of the three-roll mill is 5:8:9, and the speed of the middle roller is 400rpm~600rpm; Preferably, the rotation speeds of the second centrifugal dispersion treatment and the fourth centrifugal dispersion treatment are each independently 4000 rpm to 6000 rpm; Preferably, the second centrifugal dispersion treatment and the fourth centrifugal dispersion treatment are performed independently 2 to 4 times.

6. The preparation method according to claim 2, characterized in that, The preparation method of the first glass powder includes: first mixing B2O3, SiO2, Bi2O3 and PbO, and performing a first calcination treatment to obtain a molten glass liquid; placing the molten glass liquid in water for a first water quenching treatment to obtain glass slag; and performing a first ball milling treatment on the glass slag to obtain the first glass powder. Preferably, the temperature of the first calcination treatment is 1000℃~1100℃; Preferably, the heating rate of the first calcination treatment is 20℃ / min to 30℃ / min; Preferably, the first calcination treatment time is 30 min to 90 min.

7. The preparation method according to claim 2, characterized in that, The preparation method of the second glass powder includes: mixing CuO, SiO2, Mn2O3 and ZnO, and performing a second calcination treatment to obtain a molten glass liquid; placing the molten glass liquid in water for a second water quenching treatment to obtain glass slag; and performing a second ball milling treatment on the glass slag to obtain the second glass powder. Preferably, the temperature of the second calcination treatment is 1200℃~1400℃; Preferably, the heating rate of the second calcination treatment is 10℃ / min to 30℃ / min; Preferably, the second calcination treatment time is 60 min to 120 min.

8. The preparation method according to claim 2, characterized in that, The preparation method of the first organic carrier and the second organic carrier includes: stirring and mixing the resin and the organic solvent to obtain the first organic carrier and the second organic carrier; Preferably, the stirring speed is 300 r / min to 800 r / min; Preferably, the mixing temperature is 60℃~90℃; Preferably, the mixing time is 8h to 12h.

9. The preparation method according to claim 1, characterized in that, The sintering temperature is 720℃~780℃; Preferably, the sintering heating rate is 3℃ / min to 10℃ / min; Preferably, the sintering time is 6h to 12h.

10. A silver-nickel-copper ternary composite electrode for a back-contact photovoltaic cell, characterized in that, The silver-nickel-copper ternary composite electrode of the back contact photovoltaic cell is prepared by the preparation method according to any one of claims 1 to 9; The silver-nickel-copper ternary composite electrode comprises a silver-based ohmic contact layer, a nickel-based diffusion barrier layer, and a copper-based conductive layer stacked sequentially.

Citation Information

Patent Citations

  • Silver-nickel conductive paste for BC battery and preparation method of silver-nickel conductive paste

    CN120164656A

  • Back contact solar cell, preparation method thereof and photovoltaic module

    CN121908688A